2002
DOI: 10.1002/tal.195
|View full text |Cite
|
Sign up to set email alerts
|

Field measurements of amplitude‐dependent damping in a 79‐storey tall building and its efects on the structural dynamic responses

Abstract: This paper describes some results obtained from full-scale measurements of wind effects on a super-tall building, Di-Wang Tower, located in Shenzhen, China. This tall building has 79-storeys with a height of approximately 324 m. Field measurements including wind speed, wind direction and wind-induced acceleration responses have been made. The amplitude-dependent characteristics of damping are obtained by using the random decrement technique from the detailed analysis of the field acceleration measurements. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 10 publications
(9 reference statements)
4
13
0
Order By: Relevance
“…Ventura et al (2002) used ambient vibration results to update a FE model of a building including non-structural elements. Li et al (2002) highlighted that measured natural frequencies of a 79 storey building were higher than those calculated from the FE model, concluding that this difference was due to the presence of non-structural elements.…”
Section: Introductionmentioning
confidence: 93%
“…Ventura et al (2002) used ambient vibration results to update a FE model of a building including non-structural elements. Li et al (2002) highlighted that measured natural frequencies of a 79 storey building were higher than those calculated from the FE model, concluding that this difference was due to the presence of non-structural elements.…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, the identification is performed on quasi-static loadings whereas damping ratio is used for seismic loadings. In addition, several studies have emphasized the fact that the viscous damping depends on the response amplitude for RC buildings [11,12,8], which contradicts the hypothesis of a linear equivalent viscous damping. To verify if the previous observations made on buildings comply with RC components, beams in the present study, and evaluate the influence of different excitation and material parameters, an experimental campaign described in the following section has been carried out and is followed by numerical experiments calibrated on experimental data.…”
Section: Introductionmentioning
confidence: 98%
“…Such tests have been widely used to extract modal properties from structures (Ceravolo and Abbiati, 2012;Beskhyroun et al, 2013;Farrar and James III, 1997;Magalhães et al, 2010;Snaebjörnsson and Ingolfsson, 2013). Jeary (1992Jeary ( , 1996 showed that outputonly techniques can be used not only to assess the modal properties of such structures, but also how those properties vary with amplitude of vibration, and his work led to studies to quantify that variation for tall buildings as wind speed varies (Li et al, 2002(Li et al, , 2003Tamura and Suganuma, 1996). In this study, the building was tested at two stages during construction, which allowed analysis of the influence of the non-structural elements added between the two tests on the measured modal properties.…”
Section: Introductionmentioning
confidence: 99%